Determination of cocaine in spiked saliva using liquid-liquid extraction and gas chromatography-mass selective detector methods - Mohamed Inas Abdul Latheef, 1983-, author 620505 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Sains : Sains Forensik) - Universiti Teknologi Malaysia, 2019